OSCILLATOR MODEL OF INTERACTION WITHIN A SMALL SOCIAL GROUP IN INDUSTRY AND TRANSPORT - A. I. Ivanov (Научный вестник МГТУ ГА, 2016)
The article deals with the issues of self-organization in small groups for example, personnel of industry and transport enterprises, including aviation and aircraft crew. Van der Pol non-linear dissipative oscillator is the basis of interaction in a small group model. The model describes interaction between the group members through synchronization of oscillators, which allows to take into account interaction, and counteraction, and coexistence of two types of interactions as the complex nature of unity and struggle of opposites for a selected center of interaction as a compulsory attribute of a small group.